2020. COVID-19 and Its Ghosts at Our Doorsteps: Transformations, Opportunities and Limits. Issue 3 (3rd July 2021) - Pulcini, Valeria
ABSTRACT: The critical and dark period we are still experiencing is shared by everyone in the world. The pandemic in fact burst into private, social and working lives of all human beings. In telling a year-long story, my intent is to share what happened in my subjective reality, and my work as an analyst in Italy. The unsettling storm in the beginning, the vortex of changes in the setting, and the inner earthquake of questions and uncertainties, are feelings and experiences that are likely to recall analogies, memories or nightmares. My therapeutic work, at the time, focused on the pondered yet unthought processing and transformation of the sessions, in a dance between an ancient certainty and a new uncertainty, yet to experiment. In the ancient certainty lies the therapeutic dyad with its own subjectivity, story, and the need to be empathic and affective witnesses when it's the hardest. In the uncertainty of the new, I have discovered the capability and the fear of losing myself, searching for an opening to be with my patients again, in the various paths, in similarities and differences, in shared pain and surprise. It is not over yet, but the light of the great thinkers and the closeness and support of my psychoanalytic community, have given me strength and hope in bearing the weight of these moments, and in keeping my consciousness and conscience awake for the reconstruction of the value of the interhuman world.